Yellowstone wildlife : ecology and natural history of the greater Yellowstone ecosystem - Johnsgard, Paul A. (University Press of Colorado, 2013)
This book is a natural history of the wildlife species that call Yellowstone National Park and the Greater Yellowstone Ecosystem their home. Illustrated with images shot by a professional wildlife photographer, the book describes the lives of species in the park, exploring their habitats from the Grand Tetons to Jackson Hole. From charismatic megafauna like elk, bison, wolves, bighorn sheep, and grizzly bears, to smaller mammals like bats, pikas, beavers, and otters, to some of the 279 species of birds, the author describes the behavior of animals throughout the seasons, with sections on what summer and autumn mean to the wildlife of the park, especially with the intrusion of millions of tourists each year.